Høy Ædle Hr. Biskop. Præsteindberetninger om jordskælvet 21.-22. Dec. 1759. Del 1 - Bondesen, Erling (Historisk Årbog for Roskilde Amt, 2020)
Høy Ædle Hr. Biskop. Præsteindberetninger om jordskælvet 21.-22. Dec. 1759. Del 1